Production of 4-keto-D-arabonate by oxidative fermentation with newly isolated Gluconacetobacter liquefaciens - Adachi, Osao (2010)
Production of 4-keto-D-arabonate (4KAB) was confirmed in a culture medium of Gluconacetobacter liquefaciens strains, newly isolated from water kefir in Argentina. The strains rapidly oxidized D-glucose, Dgluconate (GA), and 2-keto-D-gluconate (2KGA), and accumulated 2,5-diketo-D-gluconate (25DKA) exclusively before reaching the stationary phase. 25DKA was in turn converted to 4KAB, and 4KAB remained stable in the culture medium. The occurrence of 4KAB was assumed by Ameyama and Kondo about 50 years ago in their study on the carbohydrate metabolism of acetic acid bacteria (Bull. Agr. Chem. Soc. Jpn., 22, 271-272, 380-386 (1958)). This is the first report confirming microbial production of 4KAB.